Photoelectrochemical Immunosensor Based on ZnIn2S4/Bi2Se3 Nanocomposite for the Determination of Cardiac Troponin I. (12th August 2020) - Dong, Wanxin; Mo, Xinxin; Wang, Yu; Lei, Qin; Li, He
Abstract: In this work, a novel flexible photoelectrochemical immunosensor is developed to determine cardiac troponin I (cTnI) in serum. The flower-like ZnIn2 S4 nanospheres (ZIS), as signal amplification material, were successfully synthesized by a solvothermal method. The ZIS and Bi2 Se3 were modified on the indium tin oxide- polyethylene terephthalate (ITO-PET) electrode, which effectively accelerates the electronic transition and improved the photocurrent conversion efficiency (signal on). However, the binding of antigen–antibody proteins blocks the electron transfer, resulting in a greatly reduced photocurrent (signal off). By adding the second antibody modified by CdSe quantum dots (CdSe QDs-Ab2 ), the photocurrent is increased (signal on). The constructed immunosensor has a linear range from 0.08 to 40 ng/mL with a detection limit of 0.026 ng/mL, which shows excellent selectivity, high sensitivity, and good stability. The photoelectrochemical immunosensor has broad application prospects for the clinical examination of myocardial infarction.